Klasifikasi Tingkat Kepuasan Siswa Sekolah Dasar Pada Pembelajaran Matematika Berbasis Animasi Menggunakan Algoritma Decision Tree - Alvina Damayanti; Ucok Darmanto Soer; Edora Edora (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Mathematics learning at SDN Sukamanah 01 shows low student participation due to conventional teaching methods that are predominantly one-way and lack student engagement. To address this, this study specifically evaluates the effectiveness of animation media in improving student learning satisfaction. A total of 500 student response data were analyzed using a Decision Tree algorithm to classify student satisfaction levels towards animation-based learning methods. The classification results show that the majority of students gave positive responses, with 45.6% being in the